Fracionamento de fósforo em função do modo de aplicação da adubação fosfatada e biosolubilizador - Tres, Gessika (2024)
The high weathering of Oxisols promotes high adsorption of phosphates from mineral fertilization. The mode of P application and the use of solubilizing bacteria can influence P availability in the soil. The objective of the work was to evaluate the response of crops and changes in the forms of inorganic and organic P as a result of the modes of application of phosphate fertilizer and the use of the Biomaphos® solubilizer. The design was randomized blocks in subdivided plots: plot-application method (100% P broadcast on surface, 100% in sowing line, ½ broadcast and ½ in sowing line and, without P); subplot – with and without Biomaphos®), with seven replications. The soil under study was the Distroferric Red Latossol. Liming and plastering were carried out, with the sequence of crops, Brachiaria cv. marandu, soybeans, winter crop mix, beans and millet. For the first study, soil collection occurred after the sequence of crops and for the second study, it was collected before and after the crops, at 5 points per subplot (2 lines and 3 between lines), for a composite sample at depths (0-0,05; 0,05-0,10 and 0,10-0,20 m), performing Bowman fractionation. For the third study, soybean and bean crops were evaluated in relation to productivity, P content in the grain and leaf and, in the soil, the fractionation of inorganic P (PiH2O, PiAl, PiFe and PiCa), collecting the soil adhered to soybean and bean roots at stage R.1. For productivity, the use of Biomaphos® increased one bag per hectare in soybeans and two in beans. The lowest average P content in the grains occurred in the treatment without P. The application method changed the Pi fractions in the crops, especially when applied 100% in sowing line or ½ in the line. In beans, without added P, there was an increase in the PiFe fraction and a decrease in PiCa, influenced by the use of Biomaphos®. The location of P in line provided a higher total Pi content. The moderately labile fraction (P-H+) promoted a greater contribution to the soil's total P. There was greater dependence on organic fractions, after the crop cycle, for 100% in sowing line fertilization. Biomaphos® promoted depletion of residual P at a depth of 0,10-0,20 m after the cultivation sequence and, in the absence of phosphate fertilizer, there was an increase in organic P at a depth of up to 0,05 m. When applying phosphate fertilizer ½ at broadcast plus ½ in line, the use of Biomaphos® compared to the initial content, promoted depletion of the fractions moderately labile organic P (PoH+), total Po and %Po, for the depths from 0-0,05 m and 0,10-0,20 m.